Hotel Transylvania 3 “A Monster Vacation” Movie: Exploring Dialogue and Emotional Literacy - Arnoi, Khoirun Nisaa; Rahmah, Ilma Yullinda; Ridhawati, Listya Arum; Safi'i, Muhamad (Linguistics and ELT Journal, 2025)
This qualitative study employed content analysis to classify and critically interpret the illocutionary acts in the animated film Hotel Transylvania 3: "Summer Vacation". Based on Searle's taxonomy applied to 65 utterances, Expressive acts were found to be overwhelmingly dominant at 43%, indicating that the dialogue prioritizes relational and emotional work over purely transactional exchange. This high frequency is interpreted as an active strategy for interactional achievement, as explained by Haugh and Culpeper's theory, essential for managing interpersonal bonds within the narrative. The study's primary contribution lies in its conceptual synthesis, integrating Searle's classical classification with contemporary critical theoretical tools (Haugh, Culpeper, Trosborg) to provide a more comprehensive and critically assessed understanding of pragmatic function in cinematic discourse. Theoretically, this work supports the move toward dynamic, interactional pragmatics by demonstrating the limitations of static taxonomies in analyzing media discourse. In practice, the findings offer valuable insights for language educators and media producers on how animated film dialogue explicitly models complex relational communication and emotional literacy.